RADI-02. Hippocampal-sparing whole brain volumetric modulated arc therapy (VMAT) planning in Monaco: a "How-to" not pull your hair out. (9th August 2021) - Goss, Matthew; Rowles, Rochelle; Spanovich, Lisa; Wegner, Rodney; Hasan, Shaakir; Horne, Zachary
Abstract: Purpose: NRG-CC001 recently reported positive results on hippocampal-sparing IMRT (HS-IMRT) in conjunction with memantine for the reduction in cognitive decline compared to conventional whole brain radiation therapy. Herein, we report our experience in planning volumetric modulated arc therapy (VMAT) cases in Monaco® with the anticipation of increased utilization of the planning technique for delivery on Elekta linear accelerators. Methods and Materials: Twelve patients previously treated with whole brain radiation therapy who would have been eligible for NRG-CC001 were replanned with VMAT HS-IMRT for to a dose of 30Gy/10fx using constraints from the trial. Results: All twelve patients were able to be planned with VMAT and achieve NRG-CC001 dose constraints. Median maximum and D100% to the right and left hippocampi were: 13.37Gy and 13.43Gy, respectively and 8.76Gy and 8.86Gy, respectively. Median coverage of the brain minus the hippocampi with 30Gy was 96.53%. All cases passed quality assurance testing with 3%/3mm and 2%/2mm criterion. Conclusions: Hippocampal-sparing IMRT whole brain radiation therapy can be feasibly planned with VMAT technique in Monaco® and delivered on Elekta linear accelerators.